1997
DOI: 10.1094/phyto.1997.87.12.1250
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Improves Biocontrol of Fusarium Crown and Root Rot of Tomato by Pseudomonas fluorescens and Represses the Production of Pathogen Metabolites Inhibitory to Bacterial Antibiotic Biosynthesis

Abstract: Crown and root rot of tomato caused by Fusarium oxysporum f. sp. radicis-lycopersici is an increasing problem in Europe, Israel, Japan, and North America. The biocontrol agent Pseudomonas fluorescens strain CHA0 provides only moderate control of this disease. A one-time amendment of zinc EDTA at 33 mug of Zn(2+)/ml to hydroponic nutrient solution in soilless rockwool culture did not reduce disease when used alone, but did reduce disease by 25% in the presence of CHA0. In in vitro studies with the pathogen, zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
129
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(145 citation statements)
references
References 36 publications
15
129
0
1
Order By: Relevance
“…The first example of interference of a soil-borne pathogenic fungus with the biosynthesis of an antimicrobial compound in a beneficial bacterium was described by Duffy and Défago (1997). In their study, DAPG biosynthesis in fluorescent Pseudomonas strain CHA0 was repressed by F. oxysporum f.sp.…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The first example of interference of a soil-borne pathogenic fungus with the biosynthesis of an antimicrobial compound in a beneficial bacterium was described by Duffy and Défago (1997). In their study, DAPG biosynthesis in fluorescent Pseudomonas strain CHA0 was repressed by F. oxysporum f.sp.…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%
“…radicis-lycopersici. Fusaric acid produced by Fusarium was shown to be the fungal metabolite that specifically repressed DAPG biosynthesis (Duffy and Défago 1997;Notz et al 2002): blocking fusaric acid production in Fusarium by addition of zinc relieved repression of the phlA gene and improved the activity of strain CHA0. Subsequent studies showed that among a collection of genotypically different DAPG-producing Pseudomonas strains, several were relatively insensitive to fusaric acid-mediated repression of DAPG biosynthesis (Duffy et al 2004).…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%
“…In the present study, Mn was negatively correlated with disease suppression by 2-79; this may be related to the ability of 2-79 to either oxidize or reduce Mn under different soil conditions. The interaction between a plant pathogen and a biocontrol agent (8) can be influenced by soil properties. Fusaric acid produced by the phytopathogenic fungus Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, commercial application of these bacteria for biocontrol has been hampered in large part because of their inconsistent performance between field locations (45). Such variability has been attributed to different causes, including host plant genotype (37,44), agricultural practices (28), mutation of the biocontrol strain (7), pathogen resistance to biocontrol mechanisms (23), and vulnerability of the biocontrol strain to pathogen defense mechanisms (8). For biocontrol strains of Pseudomonas fluorescens, antibiotic production often plays a central role in disease control (40).…”
mentioning
confidence: 99%
“…The suppression of Fusarium wilt of tomato was enhanced when P. putida AP-1 was applied together with methionine than AP-1 alone (50). The use of zinc also improved the biological control of Fusarium root and crown rot of tomato by P. fluorescens (7). Thereby, the amendment of soil with organic matter or a substrate in the appropriate amount likely improves the rhizosphere competence and the survival of introduced or naturally occurring antagonists in the soil, resulting in effective and sustainable disease control.…”
mentioning
confidence: 99%